Development Of Agricultural Loans In Latakia Governorate During The Period (2000-2022) (Latakia University Journal -Biological Sciences Series, 2024)
The research aimed to determine the most important changes that occurred in the total agricultural loans granted to farmers in Latakia Governorate during the period 2000-2022, and to estimate the general trend in the development of the volume of agricultural loans during the period (2023-2030) through developing a standard model to predict the volume of agricultural loans using moving average models. and autoregressive (ARIMA).The research adopted the descriptive analytical approach in studying and describing the time series of agricultural loans using tables, arithmetic averages, and percentages. The Box-Jenkins methodology was adopted in estimating the most appropriate (ARIMA) model for the purpose of predicting the volume of agricultural loans during the period (2023-2030).The results of the research showed that the total agricultural loans granted to farmers in Latakia Governorate took a random trend between increase and decrease during the period (2000-2022), and the results of the time series analysis according to the Box-Jenkins methodology showed that the (ARIMA) model (1.1.0) is the best model. To predict the volume of agricultural loans during the coming period, it is a first-order autoregressive integral model at the first difference.The results of forecasting the volume of loans granted to the agricultural sector during the period (2023-2030) showed a general increasing trend with a relatively low annual growth rate (0.30)%, which does not correspond to the general rise in the prices of production inputs that exceeded 100%, which makes them unable to meet the growing needs of farmers